Estimated effect of rotational components of seismic impact on the strength-strain state of simple systems - O. V. Mkrtychev; A. A. Reshetov; E. M. Lokhova (Vestnik MGSU)
Introduction. At the present time, when calculating structures for seismic effects, usually only the translational components of seismic effects are taken into account. However, the analysis of emerging defects in buildings and structures subjected to seismic action indicates the spatial nature of structural behavior, which indicates the necessity to take into account also the rotational components of seismic action in the design of all buildings and structures in seismic regions. The objective of this study is to assess the influence of rotational components on the stress-strain state of simple systems. In the scope of this study, the rotational components of accelerograms are obtained from both the action of only one translational component and from the action of two translational components of seismic action for an integral seismic motion model; and the equation of motion has been derived considering them.Materials and methods. The differential equations of motion for the investigated systems were solved in both planar and spatial settings. The problem in the plane formulation was solved using the central differences method in LS-DYNA software and the fourth-order Runge – Kutta method in the MATLAB software, considering one translational component and also considering one translational and one rotational component. The problem in the spatial setting was solved in the LS-DYNA software, considering only three spatial components and also considering three translational and three rotational components.Results. During the study, maximum and minimum displacement values and von Mises stress values were obtained, resulting from the action of only translational components and from the combined action of translational and rotational components.Conclusions. Based on the results of the study, a comparative analysis was conducted, leading to the conclusion that the influence of rotational components of seismic action on the stress-strain state of the investigated systems is insignificant. However, the increase in the contribution of rotational components to the stress-strain state of the system is proportional to its height.